2020
DOI: 10.1177/0954408920951728
|View full text |Cite
|
Sign up to set email alerts
|

The performance of airlift pump for the solid particles lifting during the transportation of gas-liquid-solid three-phase flow: A comprehensive research review

Abstract: Research about the enhancement of the airlift pump performance by changing the geometry and operational parameters has drawn considerable attention in recent years. This paper presents a comprehensive review of some published research articles on the enhancement performance of the airlift pump and the future direction of the research. In the introductory section, the description, the application, and the performance of the airlift pump are described. The influencing parameters of the airlift pump performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…However, in their calculations, they considered the pipe as a whole and neglected changes in air density along the flow direction. Catrawedarma et al 17 presented a comprehensive review of the literature on both air-water two-phase and air-water-solid three-phase ALPs. They divided the influencing parameters into geometric and operational categories.…”
Section: Introductionmentioning
confidence: 99%
“…However, in their calculations, they considered the pipe as a whole and neglected changes in air density along the flow direction. Catrawedarma et al 17 presented a comprehensive review of the literature on both air-water two-phase and air-water-solid three-phase ALPs. They divided the influencing parameters into geometric and operational categories.…”
Section: Introductionmentioning
confidence: 99%
“…However, the usability of the formula (1) in optimization of airlift operating condition is determined by the accuracy of ṁg and ṁl estimates. While ṁg can be set, ṁl is determined by the airlift flow regime: bubble, projectile, flowing, and annular [2,4]. It has been shown that the most effective modes for the transfer of liquid suspensions are projectile and flowing.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of modeling the three-phase flow and our focus on formulating a computationally feasible model, the tree-phase flow was replaced by a two-phase model at the current stage of research. The approach of modeling a three-phase flow as a two-phase flow is not new and has been used by many authors, e.g., [4,6]. The main idea here is that the flow characteristics in the three-phase system are similar to those of the two-phase airlift pump system.…”
Section: Introductionmentioning
confidence: 99%
“…Airlift pumps are used to transport liquids or slurries (liquid-solid) in different technologies, such as transporting different gravels and a drainage system in mining, treating urban wastewater, and transporting radioactive and corrosive solutions in the chemical industry [1]. Despite its low efficiency (only 10% to 30%) compared to other types of pumps (eccentric, screw piston, diaphragm etc.…”
Section: Introductionmentioning
confidence: 99%